Adjusting culture conditions to isolate thraustochytrids from temperate and cold environments in southern Argentina - Rosa, Silvina Mariana (2011)
To study thraustochytrids from temperate and cold environments of Southern Argentina, the standard cultivation methodologies have been modified because many of the microorganisms detected by microscopic examination in both the original samples and the colonized baits failed to be successfully isolated in standard culture media. As a result, 35 strains, most of them having a very low growth rate, were isolated. Alternative procedures are proposed according to the nature of the sample, the characteristics of the thraustochytrid to be isolated, and the presence of contaminating microorganisms. Modifications proposed include the use of a newly formulated culture medium (Mar Chiquita, containing glucose, gelatine hydrolysate, peptone, and corn steep liquor as main carbon and nitrogen sources). In addition, the effects of the nutrient composition and agar concentration of culture media on the relative growth rates of the isolates were studied in an attempt to determine the most suitable conditions for the cultivation of new strains of thraustochytrids. The goal of this study is to develop a standard methodology, allowing us to grow baitable elusive thraustochytrid strains, and that could be applied to improve the isolation and the study of the undocumented biodiversity of this group of microorganisms from different environments.